Case Report: Oxytocin and Its Association With Psychotherapy Process and Outcome - Grossman-Giron, Ariella; Tzur Bitan, Dana; Zilcha-Mano, Sigal; Nitzan, Uri; Mendlovic, Shlomo; Maoz, Hagai (Frontiers in Psychiatry, 2021)
The potential of Oxytocin (OT) as a facilitator of psychotherapy has been previously acknowledged, nonetheless, randomized controlled trials thus far have not yielded conclusive results. One approach suggested to clarify empirical inconsistencies is to refine the study hypotheses and data collection process by utilizing an in-depth idiographic exploration of the investigated phenomena. In this case illustration we provide an in-depth analysis comparing two patients hospitalized in a closed psychiatric ward with depression and undergoing psychotherapy twice a week. These two patients were randomly allocated to receive either OT or placebo, twice a day for a period of four weeks. Both patients completed longitudinal assessments of process and outcome measures, and therapists’ clinical notes were extracted and reviewed. Reliable clinical change was calculated for all outcome and process measures. The results indicated that the patient receiving OT showed significant improvement in interpersonal distress, as well as in anxiety and depression symptoms, while the placebo patient showed no significant change during the study period. Furthermore, while both patients showed no significant changes in the therapeutic alliance ratings, the therapist of the OT patient regularly reported positive changes in alliance in the medical notes, while no such report was observed in the placebo patient. These results suggest that changes produced by OT administration may be more noticeable by the therapist. Implications for future studies aimed at assessing the effect of OT on psychotherapy process and outcome are discussed.